SISTEM PENENTU KEPUTUSAN PEMILIHAN KONTEN YOUTUBE LAYAK TONTON UNTUK ANAK DENGAN METODE ARAS (ADDITIVE RATIO ASSESSMENT) BERBASIS WEB - Jimly Assidiqi , Achmad; Setyo Permadi , Ginanjar (Inovate, 2023)
This research aims to assist parents in monitoring what their children watch on the YouTube platform. YouTube is a social media site which allows users to watch and share videos. However, due to the large number of videos that are inappropriate for children, such as those containing violence, pornography, or other bad things, it is important for parents to choose appropriate and safe content. The ARAS (Additive Ratio Assessment) method is used this research as a decision system that assists in selecting content that is appropriate for children to watch. DSS (Decision support systems) play an important role helping parents overcome the problem of selecting appropriate content for their children. This can help parents make accurate and targeted decisions. This study found that of the 15 alternatives that have been selected, the highest ranking is Nussa animation with a Ki value of 1, followed by Pada Zaman Dahulu animation with a Ki value of 0.8425. Therefore, this research suggests Nussa animation as a worthy spectacle for children. Keywords: SPK, ARAS Method, Youtube, Children.